Si Satchanalai Historical Park Ancient Monuments Compound Announcement: Processes and Results - Rujirotvarangkul, Chitsanupong (NAJUA: History of Architecture and Thai Architecture, 2022)
This article aims to discuss the processes and results caused by the Fine Arts Department's boundary announcement of Si Satchanalai historical park in 1988. The research draws upon documents of the historical park project, master plans, related laws, and interviews with residents in Si Satchanalai historical park area. The research on a community in Si Satchanalai historical park conducted by a master plan committee proposed that the Fine Arts Department should prioritize each area of the ancient monuments compound to be protected. Therefore, it was unnecessary to announce the whole ancient monuments compound as one. However, the Fine Arts Department announced the boundary that covered the entire area of 28,217 rai, which directly impacted building construction in ancient monuments compound and land mortgage. Furthermore, the announcement forced Yom riverside communities to change their way of life and another community nearby the ancient monuments to relocate. These incidents indicated the power over ancient monuments compound of the Fine Arts Department and legal processes according to an Act on Ancient Monuments, Antiques, Objects of Art and National Museums 1961 without consideration of the research results from every aspect and concern about stakeholders. Accordingly, it is important to reconsider the announcement processes of ancient monuments in the future.